Epigenetic Modulation of Microglia Function and Phenotypes in Neurodegenerative Diseases - Li Wang; Chao-Chao Yu; Xin-Yuan Liu; Xiao-Ni Deng; Qing Tian; Yan-Jun Du (Neural Plasticity)
Microglia-mediated neuroinflammation is one of the most remarkable hallmarks of neurodegenerative diseases (NDDs), including AD, PD, and ALS. Accumulating evidence indicates that microglia play both neuroprotective and detrimental roles in the onset and progression of NDDs. Yet, the specific mechanisms of action surrounding microglia are not clear. Modulation of microglia function and phenotypes appears to be a potential strategy to reverse NDDs. Until recently, research into the epigenetic mechanisms of diseases has been gradually developed, making it possible to elucidate the molecular mechanisms underlying the epigenetic regulation of microglia in NDDs. This review highlights the function and phenotypes of microglia, elucidates the relationship between microglia, epigenetic modifications, and NDDs, as well as the possible mechanisms underlying the epigenetic modulation of microglia in NDDs with a focus on potential intervention strategies.